Adopting building automation in weblabs - Costa, Ricardo J. (2017)
Several companies have been developing domotic Stds. for building automation, enabling users to locally and remotely control several home devices, like: lights, power sockets, heating, ventilation, and air conditioning systems, among others. Besides contributing to improve the building comfort, these Stds. may also be adopted for other purposes, namely in weblabs used in sciences and engineering remote experiments. To increase the sense of immersion in weblabs, we identify domotic Stds. as a standard solution for turning on/off the power infrastructure and controlling the light and temperature conditions of the physical space where a specific experiment may run, thus approaching the sense of being in the lab facilities while accessing them through the corresponding weblab interface. After identifying the added value to weblabs in terms of power savings and in the control of the environmental conditions, we used our knowledge and the WWW to conduct an extensive search on domotic Stds., and after analysing the results obtained, we choose the most appropriated one to be implemented in a Weblab. Regarding the adopted Std., a proof-of-concept is also described, enabling the control of an halogen lamp and a power socket, using a specific Web interface.